**Answer: The term to term rule is an Arithmetic progression for the two question. B) 1Oth term for the first is 30 and for the second series is 59**

**Step-by-step explanation:**

**4.1**) 3 6 9 12 15

For the sequence above, we can see that the next term is gotten by addition of 3 with the previous term and so It is an Arithmetic progression.

Having in mind the nth term of an AP as Tn = a + (n - 1)d.

where a is the first term =3

And d common difference =3(6-3,9-6,12-9)

10th term=

T10 = 3+ (10 - 1)3.

T10 = 3+ (9)3.

T10 = 3+ 27.

T10 =30

**4.2)** 5 11 17 23 29

For the sequence above, we can see that the next term is gotten by addition of 6 with the previous term and so It is an Arithmetic progression.

Having in mind the nth term of an AP as Tn = a + (n - 1)d.

where a is the first term =5

And d common difference =6 (11-5, 17-11,23-17)

10th term=

T10 = 5+ (10 - 1)6.

T10 = 5+ (9)6.

T10 = 5+ 54.

T10 =59